2020
DOI: 10.1063/1.5131432
|View full text |Cite
|
Sign up to set email alerts
|

Performance prediction of PV modules based on artificial neural network and explicit analytical model

Abstract: The accurate characterization and prediction of current-voltage characteristics of photovoltaic (PV) modules under different operating conditions is essential for solar power forecasting and ensuring grid stability. The traditional method based on the single-diode model is inconvenient and complex because the current-voltage equation is implicit. In this paper, a novel method combining an artificial neural network (ANN) with an explicit analytical model (EAM) is proposed for predicting the I-V characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is more prominent in solar experiments since researchers can postulate solar panels' performance and durability using computational tools in either simulation or practical experiments. During our screening, we found that some authors performed their studies practically in real time [35] , [36] , [58] , and many authors adopted simulation tools with curated data sets to obtain their findings [5] , [67] , [4] . In another situation, simulation and practical approaches have been applied in the same experiments for a better comparative analysis [50] , [61] , [41] .…”
Section: Resultsmentioning
confidence: 99%
“…It is more prominent in solar experiments since researchers can postulate solar panels' performance and durability using computational tools in either simulation or practical experiments. During our screening, we found that some authors performed their studies practically in real time [35] , [36] , [58] , and many authors adopted simulation tools with curated data sets to obtain their findings [5] , [67] , [4] . In another situation, simulation and practical approaches have been applied in the same experiments for a better comparative analysis [50] , [61] , [41] .…”
Section: Resultsmentioning
confidence: 99%
“…Examples of these algorithms are presented by Wang et at. [40] and Zhang et al [41]. These algorithms determine directly the optimal models used to describe the I-V curve, however, no further information can be extracted regarding the boundaries of the parameters.…”
Section: Solutions For the Sdmmentioning
confidence: 99%
“…However, the maximum power prediction based on the SDM requires firstly extraction of five parameters at reference conditions from an implicit equation that relies on current and voltage and then determine the model parameters under various temperature and irradiance conditions using set transformation equations 6‐12 . Recently, many methods have been presented based on artificial neural networks (ANNs) to predict the maximum power of PV modules 13‐15 . However, these technics have some computational problems such as higher computational complexity and cost.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Recently, many methods have been presented based on artificial neural networks (ANNs) to predict the maximum power of PV modules. [13][14][15] However, these technics have some computational problems such as higher computational complexity and cost.…”
mentioning
confidence: 99%